Ion exchange membrane with catalyst layer, ion exchange membrane, and electrolytic hydrogenation apparatus

The ion exchange membrane with a catalyst layer, featuring a specific multilayer structure, addresses the challenges of high electrolytic voltage and low current efficiency in the electrolytic hydrogenation of aromatic compounds, resulting in enhanced production efficiency.

JP2025039759AInactive Publication Date: 2025-03-21AGC INC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2025003391
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2020-02-06
Filing Date
2025-01-09
Publication Date
2025-03-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing electrolytic hydrogenation devices face challenges in reducing electrolytic voltage and improving current efficiency during the electrolytic hydrogenation of aromatic compounds.

Method used

An ion exchange membrane with a catalyst layer is developed, featuring an inorganic particle layer, a first fluoropolymer layer with a low ion exchange capacity, and a second fluoropolymer layer with a high ion exchange capacity, arranged in a specific order to enhance performance.

Benefits of technology

The proposed membrane structure reduces electrolytic voltage and increases current efficiency, thereby improving the production efficiency of hydrogenated organic matter.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025039759000014
    Figure 2025039759000014
  • Figure 2025039759000015
    Figure 2025039759000015
  • Figure 2025039759000016
    Figure 2025039759000016
Patent Text Reader

Abstract

To provide an ion exchange membrane with a catalyst layer, an ion exchange membrane, and an electrolytic hydrogenation apparatus, in which an electrolytic voltage can be low and a current efficiency can be high in an electrolytic hydrogenation of an aromatic compound.SOLUTION: An ion exchange membrane with a catalyst layer of the present invention comprises: an inorganic substance particle layer including inorganic substance particles and a binder; a layer (Sa) including a first fluorine-containing polymer having a sulfonic acid type functional group; a layer (Sb) including a second fluorine-containing polymer having a sulfonic acid type functional group; and a catalytic layer in this order. The ion exchange capacity of the first fluorine-containing polymer is lower than the ion exchange capacity of the second fluorine-containing polymer.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an ion exchange membrane with a catalyst layer, an ion exchange membrane, and an electrolytic hydrogenation apparatus. [Background technology]

[0002] As a method for producing hydrogenated organic compounds (such as cyclohexane, methylcyclohexane, and decahydronaphthalene), a method in which hydrogen is added to an aromatic compound (such as benzene, toluene, and naphthalene) in a hydrogenation reactor is known. In recent years, electrolytic hydrogenation of aromatic compounds has been considered as an alternative to the above-mentioned methods, because it can simplify the production of hydrogenated organic compounds, etc. The electrolytic hydrogenation of aromatic compounds is carried out, for example, using an electrolytic hydrogenation apparatus having a structure in which a cathode and an anode are separated by an ion exchange membrane. Patent Document 1 discloses, as an ion exchange membrane in an electrolytic hydrogenation apparatus, a cathode catalyst layer-electrolyte membrane assembly having an electrolyte membrane (product name "NRE-212CS", manufactured by DuPont, a membrane composed of a fluorine-containing polymer having sulfonic acid groups), a zirconium oxide layer provided on the anode (positive electrode) side surface of the electrolyte membrane, and a catalyst layer provided on the cathode (negative electrode) side surface of the electrolyte membrane. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Patent No. 6400410 Summary of the Invention [Problem to be solved by the invention]

[0004] In recent years, in the electrolytic hydrogenation of aromatic compounds using an electrolytic hydrogenation apparatus, there has been a demand for further reduction in electrolytic voltage and further improvement in current efficiency in order to further improve the production efficiency of hydrogenated organic compounds. The present inventors, referring to Patent Document 1, applied an ion exchange membrane with a catalyst layer having, in this order, an inorganic particle layer, a layer containing a fluorinated polymer having sulfonic acid type functional groups, and a catalyst layer to an electrolytic hydrogenation apparatus and found that there was room for improvement in at least one of the electrolytic voltage and current efficiency during the electrolytic hydrogenation of aromatic compounds.

[0005] The present invention has been made in view of the above-mentioned circumstances, and an object of the present invention is to provide an ion exchange membrane with a catalyst layer, an ion exchange membrane, and an electrolytic hydrogenation apparatus that can reduce the electrolysis voltage and increase the current efficiency during the electrolytic hydrogenation of aromatic compounds. [Means for solving the problem]

[0006] The present inventors have intensively investigated the above-mentioned problems and have found that, when an ion exchange membrane with a catalyst layer has an inorganic particle layer, a layer (Sa) containing a first fluoropolymer, a layer (Sb) containing a second fluoropolymer, and a catalyst layer in this order, and the ion exchange capacity of the first fluoropolymer is lower than that of the second fluoropolymer, the inorganic particle layer of the ion exchange membrane with a catalyst layer is arranged on the anode side and the catalyst layer of the ion exchange membrane with a catalyst layer is arranged on the cathode side, thereby achieving the present invention.

[0007] That is, the inventors discovered that the above problems can be solved by the following configuration. [1] An inorganic particle layer containing inorganic particles and a binder; A layer (Sa) containing a first fluorine-containing polymer having a sulfonic acid functional group; a layer (Sb) containing a second fluorine-containing polymer having a sulfonic acid functional group; a catalyst layer, The catalyst layer-attached ion exchange membrane, wherein the ion exchange capacity of the first fluoropolymer is lower than the ion exchange capacity of the second fluoropolymer. [2] The ion exchange membrane with a catalyst layer according to [1], which has an uneven structure at the interface of the layer (Sa) on the inorganic particle layer side. [3] The ion exchange membrane with a catalyst layer according to [1] or [2], further comprising a reinforcing material including a reinforcing thread. [4] The ion exchange membrane with a catalyst layer according to any one of [1] to [3], wherein the first fluoropolymer has an ion exchange capacity of 0.5 to 1.1 milliequivalents / gram of dry resin. [5] The ion exchange membrane with a catalyst layer according to any one of [1] to [4], wherein the second fluoropolymer has an ion exchange capacity of 0.7 to 2.0 milliequivalents / gram of dry resin. [6] The ion exchange membrane with a catalyst layer according to any of [1] to [5], wherein the first fluorine-containing polymer having a sulfonic acid type functional group contains a unit based on a fluorine-containing olefin and a unit having a sulfonic acid type functional group and a fluorine atom. [7] The catalyst-layer-attached ion exchange membrane according to [6], wherein the fluorine-containing olefin is tetrafluoroethylene, chlorotrifluoroethylene, vinylidene fluoride, vinyl fluoride or hexafluoropropylene. [8] The ion exchange membrane with a catalyst layer according to [6] or [7], wherein the unit having a sulfonic acid type functional group and a fluorine atom is a unit represented by formula (1): Equation (1) -[CF 2 -CF(-L-(SO 3 M) n )]- In the formula, L is an (n+1) valent perfluorohydrocarbon group which may contain an etheric oxygen atom, M is a hydrogen atom, an alkali metal or a quaternary ammonium cation, and n is 1 or 2. [9] An inorganic particle layer including inorganic particles and a binder; A layer (Sa) containing a first fluorine-containing polymer having a sulfonic acid functional group; a layer (Sb) containing a second fluorine-containing polymer having a sulfonic acid functional group, in this order; An ion exchange membrane in which the ion exchange capacity of the first fluoropolymer is lower than the ion exchange capacity of the second fluoropolymer.

[10] The ion exchange membrane according to [9], wherein the layer (Sa) has an uneven structure at the interface on the inorganic particle layer side.

[11] The ion exchange membrane according to [9] or

[10] , further comprising a reinforcing material including a reinforcing thread.

[12] The ion exchange membrane according to any one of [9] to

[11] , wherein the first fluoropolymer has an ion exchange capacity of 0.5 to 1.1 milliequivalents / gram of dry resin.

[13] The ion exchange membrane according to any one of [9] to

[12] , wherein the second fluoropolymer has an ion exchange capacity of 0.7 to 2.0 milliequivalents / gram of dry resin.

[14] A method for producing an ion exchange membrane with a catalyst layer according to any one of [1] to [8], comprising the steps of: A method for producing an ion exchange membrane with a catalyst layer, comprising obtaining the ion exchange membrane according to [9] and providing a catalyst layer on the layer (Sb).

[15] An electrolytic cell having an anode and a cathode; [1] to [8], and an ion exchange membrane with a catalyst layer according to any one of the above. the catalyst layer-equipped ion exchange membrane is disposed in the electrolytic cell so as to separate the anode and the cathode; an electrolytic hydrogenation apparatus, wherein the inorganic particle layer of the catalyst-coated ion exchange membrane is disposed on the anode side, and the catalyst layer of the catalyst-coated ion exchange membrane is disposed on the cathode side.

[16] The electrolytic hydrogenation apparatus according to

[15] , wherein an electrolyte aqueous solution is supplied to an anode chamber in which the anode is disposed, and an aromatic compound is supplied to a cathode chamber in which the cathode is disposed. Effect of the Invention

[0008] According to the present invention, it is possible to provide an ion exchange membrane with a catalyst layer, an ion exchange membrane, and an electrolytic hydrogenation apparatus that can reduce the electrolytic voltage and increase the current efficiency during the electrolytic hydrogenation of aromatic compounds. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a schematic cross-sectional view showing an example of a catalyst layer-attached ion exchange membrane of the present invention. [Diagram 2] FIG. 2 is a partially enlarged view of a schematic cross-sectional view showing an example of a catalyst layer-attached ion exchange membrane of the present invention. [Diagram 3] FIG. 1 is a schematic cross-sectional view showing an example of an ion exchange membrane of the present invention. [Figure 4] FIG. 1 is a schematic diagram showing an example of an electrolytic hydrogenation apparatus of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The following definitions of terms apply throughout the specification and claims.

[0011] An "ion exchange membrane" is a membrane that contains a polymer having ion exchange groups. The term "ion exchange group" refers to a group capable of exchanging at least a portion of the ions contained in this group with other ions, and examples thereof include the following carboxylic acid type functional groups and sulfonic acid type functional groups. "Carboxylic acid functional group" refers to a carboxylic acid group (-COOH) or a carboxylate group (-COOM) 1 However, M 1 is an alkali metal or quaternary ammonium base. "Sulfonic acid functional group" refers to a sulfonic acid group (-SO 3 H), or sulfonate groups (-SO 3 M 2 However, M 2 is an alkali metal or quaternary ammonium base. A "precursor layer" is a layer (membrane) that contains a polymer having groups that can be converted into ion-exchange groups. The term "group that can be converted into an ion-exchange group" refers to a group that can be converted into an ion-exchange group by a known treatment such as hydrolysis or acidification. The term "group that can be converted into a sulfonic acid functional group" refers to a group that can be converted into a sulfonic acid functional group by a known treatment such as hydrolysis treatment or acidification treatment.

[0012] The term "fluorine-containing polymer" refers to a polymer compound having fluorine atoms in the molecule. The term "perfluorocarbon polymer" refers to a polymer in which all of the hydrogen atoms bonded to carbon atoms in the polymer are replaced by fluorine atoms. A portion of the fluorine atoms in the perfluorocarbon polymer may be replaced by one or both of chlorine and bromine atoms. "Monomer" means a compound having a polymerization reactive carbon-carbon unsaturated double bond. The term "fluorine-containing monomer" means a monomer having a fluorine atom in the molecule. The term "structural unit" refers to a portion derived from a monomer that exists in a polymer and constitutes the polymer. For example, when a structural unit is generated by addition polymerization of a monomer having a carbon-carbon unsaturated double bond, the structural unit derived from this monomer is a divalent structural unit generated by cleavage of this unsaturated double bond. In addition, the structural unit may be a structural unit obtained by chemically converting, for example, hydrolyzing, a structural unit after forming a polymer having a structure of a certain structural unit. In the following, structural units derived from individual monomers may be described in terms of the name of the monomer followed by "unit" in some cases.

[0013] "Reinforcing material" refers to a material used to improve the strength of the ion exchange membrane. The reinforcing material is a material derived from a reinforcing fabric. The term "reinforcing fabric" refers to a fabric used as a raw material for a reinforcing material for improving the strength of an ion exchange membrane. The "reinforcing thread" refers to a thread that constitutes a reinforcing cloth, and is made of a material that will not dissolve even if the reinforcing cloth is immersed in an alkaline aqueous solution (for example, an aqueous solution of sodium hydroxide with a concentration of 32% by mass). The "sacrificial yarn" is a yarn that constitutes the reinforcing fabric and contains a material that dissolves in an alkaline aqueous solution and / or a process liquid (e.g., an electrolyte solution or an aromatic compound used in the electrolytic hydrogenation of an aromatic compound). The term "dissolution hole" refers to a hole formed as a result of the sacrificial yarn being dissolved in an alkaline aqueous solution. By "reinforced precursor membrane" is meant a membrane having a reinforcing fabric disposed within the precursor layer.

[0014] A numerical range expressed using "~" means that the range includes the numerical values ​​before and after "~" as the lower and upper limits.

[0015] The thickness of each layer of the ion exchange membrane with a catalyst layer when dried is determined by observing the cross section of the ion exchange membrane with a catalyst layer under an optical microscope and using image software after drying the ion exchange membrane with a catalyst layer at 90° C. For unevenness on the surface of the layer, the thickness of 10 concave portions and the thickness of 10 convex portions are measured, and the arithmetic average of the thicknesses at the 20 points in total is determined as the layer thickness. "TQ value" is a value related to the molecular weight of a polymer. 3 The volumetric flow rate is the amount of polymer flowing out per mm when the polymer is melted and allowed to flow out of an orifice (diameter: 1 mm, length: 1 mm) at a constant temperature under a pressure of 3 MPa. 3 The TQ value is expressed in units of / sec. The higher the TQ value, the higher the molecular weight. "Ion exchange capacity" is a value calculated as follows. First, the fluoropolymer is placed in a glove box flushed with dry nitrogen for 24 hours, and the dry mass of the fluoropolymer is measured. Thereafter, the fluoropolymer is immersed in a 2 mol / L aqueous sodium chloride solution at 60°C for 1 hour. The fluoropolymer is washed with ultrapure water and then removed, and the liquid in which the fluoropolymer was immersed is titrated with a 0.1 mol / L aqueous sodium hydroxide solution to determine the ion exchange capacity of the fluoropolymer.

[0016] [Ion exchange membrane with catalyst layer] The ion exchange membrane with a catalyst layer of the present invention has, in this order, an inorganic particle layer containing inorganic particles and a binder, a layer (Sa) containing a first fluoropolymer having a sulfonic acid type functional group (hereinafter also referred to as "fluoropolymer (S1)"), a layer (Sb) containing a second fluoropolymer having a sulfonic acid type functional group (hereinafter also referred to as "fluoropolymer (S2)"), and a catalyst layer. In addition, the ion exchange capacity of the fluoropolymer (S1) is lower than the ion exchange capacity of the fluoropolymer (S2). The catalyst-layered ion-exchange membrane of the present invention is preferably used for the electrolytic hydrogenation of aromatic compounds. When the catalyst-layered ion-exchange membrane of the present invention is applied to an electrolytic hydrogenation apparatus, by disposing the inorganic particle layer on the anode side and disposing the catalyst layer on the cathode side, the electrolytic voltage can be reduced and the current efficiency can be increased during the electrolytic hydrogenation of aromatic compounds. Although the details of the reason for this are not clear, it is speculated to be due to the following reasons.

[0017] In the electrolytic hydrogenation apparatus, the ion exchange membrane with the catalyst layer is disposed in the electrolytic cell so as to separate the anode chamber in which the anode is disposed from the cathode chamber in which the cathode is disposed. An electrolyte aqueous solution is supplied to the anode chamber, and an aromatic compound is supplied to the cathode chamber. When such an electrolytic hydrogenation apparatus is operated, protons (H + ) migrates to the cathode side through the catalyst-layered ion-exchange membrane, and hydrogenation of aromatic compounds occurs by proton addition near the surface of the catalyst layer. Here, the hydrogenation reaction of aromatic compounds on the cathode side occurs on the catalyst layer. Specifically, it is believed that hydrogen activated on the catalyst contained in the catalyst layer comes into contact with aromatic compounds, electrons flow into the contact, and the aromatic compounds are hydrogenated. However, if moisture is present around the catalyst, it becomes difficult for aromatic compounds to approach the reaction site around the catalyst, and as a result, activated hydrogen reacts with electrons, generating hydrogen in the cathode chamber, causing a problem of reduced current efficiency. On the other hand, an electrolyte membrane with a low ion exchange capacity is less permeable to water than an electrolyte membrane with a high ion exchange capacity, and can increase the current efficiency, but increases the electrolysis voltage. Furthermore, an electrolyte membrane with a high ion exchange capacity allows water to pass through more easily than an electrolyte membrane with a low ion exchange capacity, lowering the current efficiency, but allowing the electrolysis voltage to be reduced. Taking the above into consideration, the present inventors have found that when the electrolyte membrane has a multi-layer structure, with a layer (Sa) containing a fluoropolymer (S1) with a low ion exchange capacity arranged on the anode side and a layer (Sb) containing a fluoropolymer (S2) with a high ion exchange capacity arranged on the cathode side, the movement of water from the anode chamber to the cathode chamber is suppressed, and the current efficiency can be improved. They have also found that the use of such an electrolyte membrane makes it possible to perform electrolysis at a low voltage.

[0018] In the electrolytic hydrogenation of aromatic compounds using an electrolytic hydrogenation device, an electrolyte aqueous solution is supplied to the anode chamber, and aromatic compounds are supplied to the cathode chamber. In this case, when a catalyst-layered ion-exchange membrane having a single-layer electrolyte membrane is used, the surface of the electrolyte membrane on the anode chamber side comes into contact with the electrolyte aqueous solution, and the surface of the electrolyte membrane on the cathode chamber side comes into contact with the aromatic compounds. In this case, the catalyst-layered ion-exchange membrane may be wrinkled due to the difference in swelling degree between the opposing surfaces of the catalyst-layered ion-exchange membrane. As a result, the electrolytic voltage may increase and the current efficiency may decrease. To solve this problem, the present inventors have found that the generation of wrinkles in the catalyst layer-attached ion exchange membrane can be suppressed by arranging the layer (Sa) containing the fluoropolymer (S1) on the anode side and the layer (Sb) containing the fluoropolymer (S2) on the cathode side. This is presumably due to the following reasons. The fluoropolymer (S1) has a lower ion exchange capacity than the fluoropolymer (S2) and is therefore less likely to swell with moisture. On the other hand, the fluoropolymer (S2) has a higher ion exchange capacity than the fluoropolymer (S1) and is therefore less likely to swell with organic solvents (aromatic compounds). It is therefore believed that the degree of swelling of the fluoropolymer (S1) with moisture and the degree of swelling of the fluoropolymer (S2) with aromatic compounds are balanced, thereby suppressing the occurrence of wrinkles on the surface of the catalyst layer-attached ion exchange membrane.

[0019] Hereinafter, the catalyst layer-attached ion exchange membrane of the present invention will be described with reference to FIG. 1, however, the present invention is not limited to the contents of FIG. Fig. 1 is a schematic cross-sectional view showing an example of a catalyst-coated ion-exchange membrane of the present invention. As shown in Fig. 1, the catalyst-coated ion-exchange membrane 1 has an electrolyte 12 consisting of a layer 12A, which is a layer (Sa), and a layer 12B, which is a layer (Sb), an inorganic particle layer 14 disposed on the surface of the layer 12A, and a catalyst layer 16 disposed on the surface of the layer 12B. A reinforcing material 20 is disposed in the electrolyte membrane 12.

[0020] <Layer (Sa)> The layer 12A, which is the layer (Sa), may be any layer containing the fluoropolymer (S1), but is preferably a layer consisting only of the fluoropolymer (S1) and not containing any material other than the fluoropolymer (S1). In other words, the layer (Sa) is preferably a layer consisting of the fluoropolymer (S1). When the catalyst layer-equipped ion exchange membrane 1 is applied to an electrolytic hydrogenation apparatus described below, the layer 12A is disposed closer to the anode than the layer 12B.

[0021] The thickness of the layer 12A when dry is preferably 5 to 60 μm, more preferably 10 to 40 μm, and particularly preferably 10 to 30 μm. When the thickness of the layer 12A when dry is equal to or greater than the above lower limit, the mechanical strength of the catalyst-coated ion-exchange membrane 1 is improved and the current efficiency is more excellent. When the thickness of the layer 12A when dry is equal to or less than the above upper limit, the electrical resistance of the catalyst-coated ion-exchange membrane 1 can be kept low.

[0022] 1, the layer 12A preferably has an uneven structure at the interface on the inorganic particle layer 14 side. When the interface on the inorganic particle layer 14 side has an uneven structure, the electrolyte aqueous solution is easily supplied between the anode and the anode side of the catalyst-coated ion exchange membrane 1 (i.e., the inorganic particle layer 14 side of the layer 12A) and is easily removed. This makes it possible to suppress a decrease in the effective electrolysis area, and therefore a rise in the electrolysis voltage.

[0023] In the present invention, the uneven structure present at the interface of layer (Sa) on the inorganic particle layer side means a structure having a plurality of structures (hereinafter also referred to as "protrusions") protruding from layer (Sb) toward the inorganic particle layer in the in-plane direction, and the shortest distance from the apex of a protrusion to the lowest point of the protrusion (hereinafter also referred to as "height of a protrusion") is 2 μm or more. Fig. 2 is a partially enlarged view of a cross section of the catalyst-coated ion exchange membrane of the present invention. In the example of Fig. 2, the layer 12A has a plurality of convex portions B continuously formed at the interface on the inorganic particle layer 14 side. The height of the convex portion B corresponds to the shortest distance D1 from the position P1 corresponding to the apex of the convex portion B (convex portion B2) to the lowest position P2 of the convex portion B (convex portion B2).

[0024] The height of the protrusion is measured as follows. First, the ion exchange membrane with the catalyst layer is cut along the thickness direction, and an enlarged image (for example, 100 times) of the cross section of the ion exchange membrane with the catalyst layer is taken with an optical microscope (product name "BX-51", manufactured by Olympus Corporation). Next, the height of the convex part at the interface on the inorganic particle layer 14 side of the layer 12A (the shortest distance D1 in FIG. 2) is measured from the enlarged image.

[0025] The height of the projections is 2 μm or more, and from the viewpoint of superior current efficiency, is preferably from 2 to 80 μm, particularly preferably from 10 to 50 μm.

[0026] The convex portions are preferably formed continuously in the in-plane direction of the layer (Sa), and are preferably formed at a periodic pitch.

[0027] When the surface of the layer (Sa) on the inorganic particle layer side has an uneven structure, the average distance between the apexes of the projections is preferably 20 to 500 μm, more preferably 50 to 400 μm, and particularly preferably 100 to 300 μm, in terms of further improving the current efficiency. In the present invention, the average distance between the vertices of the convex portions means the shortest distance between the vertices of adjacent convex portions, and means the arithmetic average value between 10 different vertices. In the example of FIG. 2, the shortest distance between vertices of adjacent convex portions corresponds to the shortest distance D2 from position T1 corresponding to the vertex of convex portion B1 to position T2 corresponding to the vertex of convex portion B2 adjacent to convex portion B1. The shortest distance between the apexes of adjacent convex portions is measured using the enlarged image described above in the measurement of the height of the convex portion.

[0028] Specific examples of methods for forming a concave-convex structure at the interface of layer (Sa) on the inorganic particle layer side include a method of blasting layer (Sa), a method of hot-pressing layer (Sa) with a film or metal mold having a concave-convex structure, a method of hot-pressing layer (Sa) with solid particles and then removing the particles, a method of using a film or metal mold having a concave-convex structure when forming layer (Sa), and a method of forming layer (Sa) on a film having a concave-convex structure. Alternatively, a method may be used in which the layer (Sa), the reinforcing material, and the layer (Sb) are laminated in this order and then vacuum suction is performed, thereby forming an uneven structure on the surface of the layer (Sa) that corresponds to the surface shape of the reinforcing material. The method of using a film having an uneven structure when forming the layer (Sa) is preferable because it is relatively simple and has little impurity contamination during processing, resulting in a film with stable performance. From the viewpoints of moldability and chemical resistance, the film having a concave-convex structure is preferably made of polyethylene or polypropylene.

[0029] In the example of FIG. 1, the layer 12A has an uneven structure at the interface on the inorganic particle layer 14 side. However, this is not limiting, and the interface of the layer 12A on the inorganic particle layer 14 side does not have to have an uneven structure.

[0030] (Fluorine-containing polymer (S1)) The layer (Sa) may contain one kind of fluoropolymer (S1) alone, or may contain two or more kinds of fluoropolymers (S1). The layer (Sa) may contain a polymer other than the fluoropolymer (S1) (hereinafter also referred to as other polymer), but is preferably substantially composed of the fluoropolymer (S1). "Substantially composed of the fluoropolymer (S1)" means that the content of the fluoropolymer (S1) is 90% by mass or more based on the total mass of the polymers in the layer (Sa). The upper limit of the content of the fluoropolymer (S1) is 100% by mass based on the total mass of the polymers in the layer (Sa).

[0031] Specific examples of other polymers include one or more polyazole compounds selected from the group consisting of polymers of heterocyclic compounds containing one or more nitrogen atoms in the ring, and polymers of heterocyclic compounds containing one or more nitrogen atoms and oxygen atoms and / or sulfur atoms in the ring. Specific examples of the polyazole compound include polyimidazole compounds, polybenzimidazole compounds, polybenzobisimidazole compounds, polybenzoxazole compounds, polyoxazole compounds, polythiazole compounds, and polybenzothiazole compounds. In view of the oxidation resistance of the catalyst layer-attached ion exchange membrane, other polymers include polyphenylene sulfide resins and polyphenylene ether resins.

[0032] The fluorine-containing polymer (S1) preferably contains units based on a fluorine-containing olefin, and units having a sulfonic acid type functional group and a fluorine atom. Examples of fluorine-containing olefins include fluoroolefins having 2 to 3 carbon atoms and one or more fluorine atoms in the molecule. Specific examples of fluoroolefins include tetrafluoroethylene (hereinafter also referred to as "TFE"), chlorotrifluoroethylene, vinylidene fluoride, vinyl fluoride, and hexafluoropropylene. Among these, TFE is preferred from the viewpoints of the production cost of the monomer, reactivity with other monomers, and excellent properties of the resulting fluorine-containing polymer (S1). The fluorine-containing olefins may be used alone or in combination of two or more kinds.

[0033] As the unit having a sulfonic acid type functional group and a fluorine atom, a unit represented by formula (1) is preferred. Equation (1) -[CF 2 -CF(-L-(SO 3 M) n )]-

[0034] In formula (1), L is an (n+1) valent perfluorohydrocarbon group which may contain an etheric oxygen atom. The etheric oxygen atom may be located at a terminal position or between carbon atoms in the perfluorohydrocarbon group. The number of carbon atoms in the (n+1)-valent perfluorohydrocarbon group is preferably 1 or more, particularly preferably 2 or more, and is preferably 20 or less, particularly preferably 10 or less.

[0035] L is an (n+1)-valent perfluoroaliphatic hydrocarbon group which may contain an etheric oxygen atom, and is particularly preferably a divalent perfluoroalkylene group which may contain an etheric oxygen atom in the embodiment where n=1, or a trivalent perfluoroaliphatic hydrocarbon group which may contain an etheric oxygen atom in the embodiment where n=2. The divalent perfluoroalkylene group may be either linear or branched.

[0036] M is a hydrogen atom, an alkali metal or a quaternary ammonium cation. n is 1 or 2.

[0037] The unit represented by formula (1) is preferably a unit represented by formula (1-1), a unit represented by formula (1-2), a unit represented by formula (1-3) or a unit represented by formula (1-4). Equation (1-1) -[CF 2 -CF(-OR f1 -SO 3 M)]- Equation (1-2) -[CF 2 -CF(-R f1 -SO 3 M)]-

[0038] [ka]

[0039] [ka]

[0040] R f1 is a perfluoroalkylene group which may contain an oxygen atom between carbon atoms. The number of carbon atoms in the perfluoroalkylene group is preferably 1 or more, particularly preferably 2 or more, and is preferably 20 or less, particularly preferably 10 or less.

[0041] R f2 is a perfluoroalkylene group which may contain a single bond or an oxygen atom between carbon atoms. The number of carbon atoms in the perfluoroalkylene group is preferably 1 or more, particularly preferably 2 or more, and is preferably 20 or less, particularly preferably 10 or less.

[0042] R f3 is a perfluoroalkylene group which may contain a single bond or an oxygen atom between carbon atoms. The number of carbon atoms in the perfluoroalkylene group is preferably 1 or more, particularly preferably 2 or more, and is preferably 20 or less, particularly preferably 10 or less.

[0043] r is 0 or 1. m is 0 or 1. M is a hydrogen atom, an alkali metal or a quaternary ammonium cation.

[0044] As the unit represented by the formula (1-1) and the unit represented by the formula (1-2), a unit represented by the formula (1-5) is more preferable. Equation (1-5) -[CF 2 -CF(-(CF 2 ) x -(OCF 2 CFY) y -O-(CF 2 )z -SO 3 M)]- x is 0 or 1, y is an integer from 0 to 2, z is an integer from 1 to 4, and Y is F or CF 3 M is as defined above.

[0045] Specific examples of the unit represented by formula (1-1) include the following units, in which w is an integer of 1 to 8, and x is an integer of 1 to 5. The definition of M in the formula is as described above. -[CF 2 -CF(-O-(CF 2 ) w -SO 3 M)]- -[CF 2 -CF(-O-CF 2 CF(CF 3 )-O-(CF 2 ) w -SO 3 M)]- -[CF 2 -CF(-(O-CF 2 CF(CF 3 )) x -SO 3 M)]-

[0046] Specific examples of the unit represented by formula (1-2) include the following units, in which w is an integer of 1 to 8. The definition of M in the formula is as described above. -[CF 2 -CF(-(CF 2 ) w -SO 3 M)]- -[CF 2 -CF(-CF 2 -O-(CF 2 ) w -SO 3 M)]-

[0047] The unit represented by formula (1-3) is preferably a unit represented by formula (1-3-1), in which M is as defined above.

[0048] [ka]

[0049] R f4 is a linear perfluoroalkylene group having 1 to 6 carbon atoms, and R f5 represents a single bond or a linear perfluoroalkylene group having 1 to 6 carbon atoms which may contain an oxygen atom between carbon atoms. The definitions of r and M are as described above.

[0050] Specific examples of the unit represented by formula (1-3-1) include the following.

[0051] [ka]

[0052] As the unit represented by formula (1-4), a unit represented by formula (1-4-1) is preferable. f1 , R f2 and M is as defined above.

[0053] [ka]

[0054] Specific examples of the unit represented by formula (1-4-1) include the following.

[0055] [ka]

[0056] The unit having a sulfonic acid type functional group and a fluorine atom may be used alone or in combination of two or more kinds.

[0057] The fluorine-containing polymer (S1) may contain units based on a fluorine-containing olefin and units based on a monomer other than the unit having a sulfonic acid type functional group and a fluorine atom (hereinafter also referred to as other monomer). Examples of other monomers include CF 2 =CFR f6 (However, R f6 is a perfluoroalkyl group having 2 to 10 carbon atoms.) CF 2 =CF-OR f7 (However, R f7 is a perfluoroalkyl group having 1 to 10 carbon atoms, CF 2 =CFO(CF 2 ) v CF=CF 2 (wherein v is an integer of 1 to 3). The content of units based on other monomers is preferably at most 30 mass % based on all units in the fluoropolymer (S1) from the viewpoint of maintaining the ion exchange performance.

[0058] The ion exchange capacity of the fluoropolymer (S1) is preferably from 0.5 to 1.1 milliequivalents / gram of dry resin, more preferably from 0.6 to 1.1 milliequivalents / gram of dry resin, particularly preferably from 0.6 to 1.0 equivalents / gram of dry resin. When the ion exchange capacity of the fluoropolymer (S1) is equal to or higher than the lower limit, the electric resistance of the catalyst layer-attached ion exchange membrane 1 is lowered, and the electrolysis voltage can be lowered. When the ion exchange capacity of the fluoropolymer (S1) is equal to or lower than the upper limit, the current efficiency is superior.

[0059] <Layer (Sb)> The layer 12B, which is the layer (Sb), may be any layer containing the fluoropolymer (S2), but is preferably a layer consisting only of the fluoropolymer (S2) and not containing any material other than the fluoropolymer (S2). In other words, the layer (Sb) is preferably a layer consisting of the fluoropolymer (S2). When the catalyst layer-equipped ion exchange membrane 1 is applied to an electrolytic hydrogenation apparatus described below, the layer 12B is disposed closer to the cathode than the layer 12A. 1, the layer 12B is shown as a single layer, but may be a layer formed from a plurality of layers. When the layer 12B is formed from a plurality of layers, the types of the constituent units constituting the fluorine-containing polymer (S2) and the ratios of the constituent units having a sulfonic acid functional group may be different in each layer. When layer 12B is formed from a plurality of layers, the ion exchange capacity of the fluoropolymer (S2) contained in each layer is higher than the ion exchange capacity of the fluoropolymer (S1) contained in layer 12A. Furthermore, when layer 12B is formed of a plurality of layers, it is preferable that the layers of layer 12B are arranged so that the ion exchange capacity increases from inorganic particle layer 14 toward catalyst layer 16. This can suppress delamination between the layers constituting layer 12B.

[0060] The thickness of the layer 12B when dry (the total thickness when the layer 12B is formed of a plurality of layers) is preferably 50 to 500 μm, more preferably 50 to 200 μm, and particularly preferably 50 to 150 μm. When the thickness of the layer 12B when dry is equal to or greater than the above lower limit, the mechanical strength of the catalyst-coated ion-exchange membrane 1 is improved and the current efficiency is more excellent. When the thickness of the layer (Sb) 12B when dry is equal to or less than the above upper limit, the electrical resistance of the catalyst-coated ion-exchange membrane 1 can be kept low.

[0061] (Fluorine-containing polymer (S2)) The layer (Sb) may contain one type of fluoropolymer (S2) alone, or may contain two or more types of fluoropolymer (S2). The layer (Sb) may contain a polymer other than the fluoropolymer (S2), but is preferably substantially composed of the fluoropolymer (S2). "Substantially composed of the fluoropolymer (S2)" means that the content of the fluoropolymer (S2) is 90% by mass or more based on the total mass of the polymers in the layer (Sb). The upper limit of the content of the fluoropolymer (S2) is 100% by mass based on the total mass of the polymers in the layer (Sb). Specific examples of the polymer other than the fluoropolymer (S2) are the same as the above-mentioned polymer other than the fluoropolymer (S1) (other polymer).

[0062] As the fluoropolymer (S2), it is preferable to use a polymer similar to the fluoropolymer (S1) except that it has a different ion exchange capacity. The ion exchange capacity of both the fluoropolymer (S1) and the fluoropolymer (S2) can be adjusted by changing the content of ion exchange groups in the fluoropolymer (S1) or the fluoropolymer (S2).

[0063] The ion exchange capacity of the fluoropolymer (S2) is preferably from 0.7 to 2.0 milliequivalents / gram of dry resin, more preferably from 0.7 to 1.5 milliequivalents / gram of dry resin, even more preferably from 0.7 to 1.4 milliequivalents / gram of dry resin, particularly preferably from 0.8 to 1.4 milliequivalents / gram of dry resin. When the ion exchange capacity of the fluoropolymer (S2) is equal to or higher than the lower limit, the electric resistance of the catalyst layer-attached ion exchange membrane is lowered, and the electrolysis voltage can be lowered. When the ion exchange capacity of the fluoropolymer (S2) is equal to or lower than the upper limit, the current efficiency is superior.

[0064] When the layer (Sb) is a single layer, the absolute value of the difference between the ion exchange capacity of the fluoropolymer (S1) and the ion exchange capacity of the fluoropolymer (S2) is preferably 0.1 to 1.4 milliequivalents / gram dry resin, more preferably 0.1 to 0.65 milliequivalents / gram dry resin, still more preferably 0.1 to 0.6 milliequivalents / gram dry resin, and particularly preferably 0.1 to 0.5 milliequivalents / gram dry resin, in terms of better exerting the effects of the present invention. When the layer (Sb) is formed from a plurality of layers, the absolute value of the difference between the ion exchange capacity of the fluoropolymer (S1) and the ion exchange capacity of the fluoropolymer (S2) contained in the layer that is located closest to the layer (Sa) among the layers constituting the layer (Sb) is preferably 0.1 to 1.4 milliequivalents / gram dry resin, more preferably 0.1 to 0.65 milliequivalents / gram dry resin, and particularly preferably 0.1 to 0.5 milliequivalents / gram dry resin, in order to better exhibit the effects of the present invention. When the layer (Sb) is formed from a plurality of layers, the absolute value of the difference in ion exchange capacity of the fluoropolymer (S2) contained in each layer constituting the layer (Sb) is, in order to better exhibit the effects of the present invention, preferably from 0.1 to 0.65 milliequivalents / gram dry resin, more preferably from 0.1 to 0.5 milliequivalents / gram dry resin, and particularly preferably from 0.1 to 0.3 milliequivalents / gram dry resin.

[0065] <Inorganic particle layer> The inorganic particle layer 14 is a layer containing inorganic particles and a binder, and is disposed on the surface of the layer 12A opposite to the surface on which the layer 12B is disposed. When oxygen gas generated by electrolysis of the electrolyte aqueous solution adheres to the surface of the layer (Sa), the electrolysis voltage increases during electrolytic hydrogenation of aromatic compounds. The inorganic particle layer is provided to suppress adhesion of oxygen gas generated by electrolysis of the electrolyte aqueous solution to the surface of the layer (Sa) and suppress an increase in the electrolysis voltage.

[0066] The thickness of the inorganic particle layer 14 is preferably from 1 to 50 μm, more preferably from 1 to 30 μm, and particularly preferably from 1 to 20 μm, in terms of enabling a further reduction in the electrolysis voltage.

[0067] The inorganic particles are preferably hydrophilic. Specifically, at least one selected from the group consisting of oxides, nitrides, and carbides of Group 4 elements or Group 14 elements is preferred, and SiO 2 , SiC, ZrO 2 , ZrC is more preferable, ZrO 2 is particularly preferred.

[0068] The average particle size of the inorganic particles is preferably 0.01 to 10 μm, more preferably 0.01 to 5 μm, and even more preferably 0.5 to 3 μm. When the average particle size of the inorganic particles is equal to or greater than the lower limit, a high gas adhesion suppression effect can be obtained. When the average particle size of the inorganic particles is equal to or less than the upper limit, the inorganic particles have excellent resistance to falling off. The average particle size of inorganic particles is the 50% diameter value (D ) calculated by calculating the volume average from the particle size distribution when a dispersion of inorganic particles in a solvent is measured using a known particle size distribution measuring device (a Microtrack Bell laser diffraction / scattering particle size distribution measuring device or a device equivalent thereto) that uses the laser diffraction / scattering method as the measurement principle. 50 ).

[0069] The binder is preferably one having hydrophilicity, more preferably a fluoropolymer having a carboxylic acid group or a sulfonic acid group, and more preferably a fluoropolymer having a sulfonic acid group. The fluoropolymer may be a homopolymer of a monomer having a carboxylic acid group or a sulfonic acid group, or a copolymer of a monomer having a carboxylic acid group or a sulfonic acid group and a monomer copolymerizable with this monomer.

[0070] The mass ratio of the binder to the total mass of the inorganic particles and the binder in the inorganic particle layer (hereinafter also referred to as the "binder ratio") is preferably 0.1 to 0.5. When the binder ratio in the inorganic particle layer is equal to or higher than the lower limit, the inorganic particles have excellent resistance to falling off. When the binder ratio in the inorganic particle layer is equal to or lower than the upper limit, a high gas adhesion suppression effect is obtained.

[0071] When the surface of the layer (Sa) on the inorganic particle layer side has an uneven structure, the inorganic particle layer preferably has an uneven surface shape that follows the uneven structure of the layer (Sa) (see FIG. 1).

[0072] <Catalyst layer> Catalyst layer 16 is a layer containing a catalyst, and is disposed on the surface of layer 12B opposite to the surface on which layer 12A is disposed. Specific examples of the catalyst include a supported catalyst in which a carbon support supports a catalyst containing platinum, a platinum alloy, or a platinum having a core-shell structure, an iridium oxide catalyst, an alloy containing iridium oxide, and a catalyst containing iridium oxide having a core-shell structure. An example of the carbon support is carbon black powder.

[0073] In order to prevent the catalyst from falling off, the catalyst layer 16 may further contain a polymer having an ion exchange group. An example of the polymer having an ion exchange group is a fluorine-containing polymer having an ion exchange group.

[0074] 1 shows a so-called zero-gap structure in which the catalyst layer 16 is formed on the surface of the layer 12B, but the present invention is not limited to this, and the catalyst layer 16 may be formed on the layer 12B via another layer. In other words, another layer may be formed between the catalyst layer 16 and the layer 12B. For example, carbon felt functioning as a cathode and a gas diffusion layer may be provided on the surface of the layer (Sb), and a catalyst layer may be formed on the surface of the carbon felt.

[0075] <Reinforcement material> The reinforcement material 20 is disposed in the electrolyte 12 . The reinforcing material 20 is a material that reinforces the electrolyte membrane 12 and originates from a reinforcing cloth. The reinforcing cloth is made of warp yarns and weft yarns, and it is preferable that the warp yarns and the weft yarns are perpendicular to each other. As shown in FIG. 1, the reinforcing cloth may have a reinforcing yarn 22 and a sacrificial yarn 24, but may not have the sacrificial yarn 24.

[0076] As the reinforcing yarn 22, yarn containing a perfluorocarbon polymer is preferable, yarn containing polytetrafluoroethylene (hereinafter also referred to as "PTFE") is more preferable, and PTFE yarn consisting only of PTFE is even more preferable.

[0077] The sacrificial yarn 24 is a yarn that is at least partially dissolved by a pretreatment (e.g., a treatment in which the reinforced precursor membrane is immersed in an alkaline aqueous solution) or a process liquid (i.e., an electrolyte solution or an aromatic compound used in the electrolytic hydrogenation of an aromatic compound). In particular, it is preferable that the sacrificial yarn 24 is a yarn that dissolves in the process liquid. This makes it easy to handle the ion exchange membrane 1 with a catalyst layer from after production of the ion exchange membrane 1 until before the conditioning operation for the electrolytic hydrogenation of aromatic compounds, and also allows the electrolysis voltage to be further reduced by dissolving the sacrificial yarn 1 during operation of the electrolytic hydrogenation apparatus. Each sacrificial yarn 24 may be a monofilament made up of one filament, or a multifilament made up of two or more filaments. As the sacrificial yarn 24, a PET yarn made only of PET, a PET / PBT yarn made of a mixture of PET and polybutylene terephthalate (hereinafter also referred to as "PBT"), a PBT yarn made only of PBT, or a PTT yarn made only of polytrimethylene terephthalate (hereinafter also referred to as "PTT") is preferred, with PET yarn being more preferred.

[0078] 1, a part of the sacrificial yarn 24 remains, and elution holes 28 are formed around the undissolved filaments 26 of the sacrificial yarn 24. This makes it difficult for damage such as cracks to occur in the ion exchange membrane 1 with a catalyst layer during handling of the ion exchange membrane 1 with a catalyst layer from after production of the ion exchange membrane 1 until before the conditioning operation of the electrolytic hydrogenation of aromatic compounds, and during installation of the ion exchange membrane 1 with a catalyst layer in an electrolytic cell during the conditioning operation.

[0079] In the example of FIG. 1, an embodiment having a reinforcing material 20 is shown, but the present invention is not limited to this, and the ion exchange membrane with a catalyst layer of the present invention may not have a reinforcing material. In addition, in the example of FIG. 1, the reinforcing material 20 is disposed between the layer 12A and the layer 12B, but the position of the reinforcing material is not limited to this, and for example, the reinforcing material may be disposed within the layer 12A or within the layer 12B.

[0080] <Method of manufacturing ion exchange membrane with catalyst layer> An example of the method for producing the ion exchange membrane with a catalyst layer of the present invention is shown below. The method for producing the ion exchange membrane with a catalyst layer of the present invention preferably includes the following steps (i) to (iv). Thereby, the above-mentioned ion exchange membrane with a catalyst layer of the present invention can be obtained. Step (i): A step of obtaining a precursor membrane in which a layer (Sa') containing a fluoropolymer (S1') having a group that can be converted into a sulfonic acid type functional group and a layer (Sb') containing a fluoropolymer (S2') having a group that can be converted into a sulfonic acid type functional group are laminated in this order. Step (ii): A step of forming an inorganic particle layer on the surface of the layer (Sa'). Step (iii): A step of converting a group in the precursor membrane that can be converted to a sulfonic acid type functional group into a sulfonic acid type functional group. Step (iv): forming a catalyst layer on the surface of the layer (Sb') Here, the order of steps (i) to (iv) is not particularly limited, but it is preferable to carry out the steps in the order of step (i), step (ii), step (iii) and step (iv).The steps may also be carried out in the order of step (ii), step (i), step (iii) and step (iv).

[0081] Hereinafter, an example of the method for producing a catalyst-layered ion exchange membrane of the present invention will be described step by step.

[0082] (Step (i)) An example of a method for producing the precursor membrane is a method in which a layer (Sa') containing a fluoropolymer (S1') and a layer (Sb') containing a fluoropolymer (S2') are arranged in this order and laminated using a lamination roll or a vacuum lamination device.

[0083] The precursor membrane may be a reinforced precursor membrane having a reinforcing material including a reinforcing thread. In this case, for example, a layer (Sa'), a reinforcing material, and a layer (Sb') are arranged in this order, and a reinforced precursor membrane is obtained according to the above-mentioned method.

[0084] The surface of the layer (Sa') opposite to the surface on which the layer (Sb') is disposed may be treated to have a concave-convex structure by any of the methods described above.

[0085] By the step (iii) described below, the layer (Sa') containing the fluoropolymer (S1') is converted into a layer (Sa) containing a fluoropolymer (S1), and the layer (Sb') containing the fluoropolymer (S2') is converted into a layer (Sb) containing a fluoropolymer (S2).

[0086] The fluorine-containing polymer (S1') is preferably a copolymer of a fluorine-containing olefin and a monomer having a fluorine atom and a group that can be converted into a sulfonic acid type functional group (hereinafter also referred to as "fluorine-containing monomer (S1')."). As the method for copolymerizing the fluoropolymer (S1'), known methods such as solution polymerization, suspension polymerization and emulsion polymerization can be adopted. The fluorine-containing olefin may be any of those exemplified above, and TFE is preferred from the viewpoints of the production cost of the monomer, the reactivity with other monomers, and excellent properties of the resulting fluorine-containing polymer (S1). The fluorine-containing olefins may be used alone or in combination of two or more kinds.

[0087] The fluorine-containing monomer (S1') may be a compound having one or more fluorine atoms in the molecule, an ethylenic double bond, and a group that can be converted into a sulfonic acid type functional group. As the fluorine-containing monomer (S1'), a compound represented by formula (2) is preferred from the viewpoints of the production cost of the monomer, the reactivity with other monomers, and excellent properties of the resulting fluorine-containing polymer (S1). Equation (2) CF 2 =CF-L-(A) n The definitions of L and n in formula (2) are as described above. A is a group that can be converted into a sulfonic acid functional group. The group that can be converted into a sulfonic acid functional group is preferably a functional group that can be converted into a sulfonic acid functional group by hydrolysis. Specific examples of groups that can be converted into a sulfonic acid functional group include -SO 2 F, -SO 2 Cl, -SO 2 Br. When two A's are present in formula (2), they may be the same or different.

[0088] As the compound represented by formula (2), a compound represented by formula (2-1), a compound represented by formula (2-2), a compound represented by formula (2-3), a compound represented by formula (2-4), and a compound represented by formula (2-3) are preferred. Formula (2-1) CF 2 =CF-OR f1 -A Formula (2-2) CF 2 =CF-R f1 -A

[0089] [ka]

[0090] R in the formula f1 , R f2 , r and A are as defined above.

[0091] [ka]

[0092] R in the formula f1 , R f2 , R f3 , r, m and A are as defined above.

[0093] Formula (2-5) CF 2 =CF-(CF 2 ) x -(OCF 2 CFY) y -O-(CF 2 ) z-SO 3 M In the formula, M, x, y, z and Y are defined as above.

[0094] Specific examples of the compound represented by formula (2-1) include the following compounds: In the formula, w is an integer of 1 to 8, and x is an integer of 1 to 5. CF 2 =CF-O-(CF 2 ) w -SO 2 F CF 2 =CF-O-CF 2 CF(CF 3 )-O-(CF 2 ) w -SO 2 F CF 2 =CF-[O-CF 2 CF(CF 3 )] x -SO 2 F

[0095] Specific examples of the compound represented by formula (2-2) include the following compounds: In the formula, w is an integer of 1 to 8. CF 2 =CF-(CF 2 ) w -SO 2 F CF 2 =CF-CF 2 -O-(CF 2 ) w -SO 2 F

[0096] The compound represented by formula (2-3) is preferably a compound represented by formula (2-3-1).

[0097] [ka]

[0098] R in the formula f4 , R f5 , r and A are as defined above.

[0099] Specific examples of the compound represented by formula (2-3-1) include the following.

[0100] [ka]

[0101] The compound represented by formula (2-4) is preferably a compound represented by formula (2-4-1).

[0102] [ka]

[0103] R in the formula f1 , R f2 and A is defined as above.

[0104] Specific examples of the compound represented by formula (2-4-1) include the following.

[0105] [ka]

[0106] The fluorine-containing monomer (S1') may be used alone or in combination of two or more kinds. In the production of the fluoropolymer (S1'), in addition to the fluorine-containing olefin and the fluorine-containing monomer (S1'), other monomers may be used. Examples of the other monomers include those exemplified above.

[0107] The TQ value of the fluoropolymer (S1') is preferably in the range of 150 to 350°C, more preferably 170 to 300°C, and even more preferably 200 to 250°C, from the viewpoints of the mechanical strength and membrane formability as a catalyst layer-attached ion exchange membrane.

[0108] The fluoropolymer (S2') is preferably produced so that the ion exchange capacity of the fluoropolymer (S1) is different when converted into the fluoropolymer (S2).

[0109] (Step (ii)) The method for forming the inorganic particle layer is not particularly limited, but examples include a method of applying an inorganic particle dispersion containing inorganic particles, a binder and a solvent to the surface of the layer (Sa') and drying the applied layer of the inorganic particle dispersion. The coating conditions and drying conditions are not particularly limited, and known conditions can be used. The inorganic particles and binder contained in the inorganic particle dispersion are as described above. The solvent contained in the inorganic particle dispersion is not particularly limited, and water or an organic solvent can be used.

[0110] (Step (iii)) Specific examples of the method for converting the groups in the precursor membrane that can be converted to sulfonic acid type functional groups into sulfonic acid type functional groups include a method of subjecting the precursor membrane to a hydrolysis treatment or an acid-form treatment. Among these, the method of contacting the precursor film with an alkaline aqueous solution is preferred.

[0111] When the above-mentioned reinforced precursor film is used as the precursor film, at least a part of the sacrificial yarn contained in the reinforced precursor film is hydrolyzed and dissolved by the action of the alkaline aqueous solution.

[0112] Specific examples of the method for contacting the precursor film with the alkaline aqueous solution include a method of immersing the precursor film in the alkaline aqueous solution and a method of spraying the alkaline aqueous solution onto the surface of the precursor film. The temperature of the alkaline aqueous solution is preferably from 30 to 100° C., particularly preferably from 40 to 100° C. The contact time between the precursor film and the alkaline aqueous solution is preferably from 3 to 150 minutes, particularly preferably from 5 to 50 minutes.

[0113] The alkaline aqueous solution preferably contains an alkali metal hydroxide, a water-soluble organic solvent and water. Alkali metal hydroxides include sodium hydroxide and potassium hydroxide. In this specification, the water-soluble organic solvent is an organic solvent that is easily dissolved in water, and specifically, the solubility in 1000 ml of water (20° C.) is preferably 0.1 g or more, and more preferably 0.5 g or more. The water-soluble organic solvent preferably contains at least one selected from the group consisting of aprotic organic solvents, alcohols, and aminoalcohols, and more preferably contains an aprotic organic solvent. The water-soluble organic solvent may be used alone or in combination of two or more kinds.

[0114] Specific examples of the aprotic organic solvent include dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, and N-ethyl-2-pyrrolidone, with dimethyl sulfoxide being preferred. Specific examples of alcohols include methanol, ethanol, isopropanol, butanol, methoxyethoxyethanol, butoxyethanol, butylcarbitol, hexyloxyethanol, octanol, 1-methoxy-2-propanol, and ethylene glycol. Specific examples of amino alcohols include ethanolamine, N-methylethanolamine, N-ethylethanolamine, 1-amino-2-propanol, 1-amino-3-propanol, 2-aminoethoxyethanol, 2-aminothioethoxyethanol, and 2-amino-2-methyl-1-propanol.

[0115] The concentration of the alkali metal hydroxide in the alkaline aqueous solution is preferably from 1 to 60% by mass, particularly preferably from 3 to 55% by mass. The content of the water-soluble organic solvent in the alkaline aqueous solution is preferably from 1 to 60% by mass, particularly preferably from 3 to 55% by mass. The concentration of water in the alkaline aqueous solution is preferably 39 to 80% by mass.

[0116] After the precursor film is brought into contact with the alkaline aqueous solution, a treatment for removing the alkaline aqueous solution may be carried out. As a method for removing the alkaline aqueous solution, for example, a method for washing the precursor film that has been brought into contact with the alkaline aqueous solution with water can be mentioned.

[0117] After contacting the precursor membrane with the alkaline aqueous solution, the resulting membrane may be contacted with an acidic aqueous solution to convert the ion exchange groups into the acid form. Specific examples of the method for contacting the precursor film with the acidic aqueous solution include a method of immersing the precursor film in the acidic aqueous solution and a method of spraying the acidic aqueous solution onto the surface of the precursor film. The acidic aqueous solution preferably contains an acid component and water. Specific examples of the acid component include hydrochloric acid and sulfuric acid.

[0118] (Step (iv)) The method for forming the catalyst layer is not particularly limited, but examples include a method in which a catalyst dispersion liquid containing a catalyst, a polymer having an ion exchange group, and a solvent is applied to the surface of the layer (Sb') and the applied layer of the catalyst dispersion liquid is dried. The coating conditions and drying conditions are not particularly limited, and known conditions can be used. The catalyst and the polymer having an ion exchange group contained in the catalyst dispersion liquid are as described above. The solvent contained in the catalyst dispersion liquid is not particularly limited, and water or an organic solvent can be used.

[0119] [Ion exchange membrane] The ion exchange membrane of the present invention has, in this order, an inorganic particle layer containing inorganic particles and a binder, a layer (Sa) containing a first fluoropolymer having a sulfonic acid type functional group, and a layer (Sb) containing a second fluoropolymer having a sulfonic acid type functional group. In addition, the ion exchange capacity of the first fluoropolymer is lower than the ion exchange capacity of the second fluoropolymer.

[0120] Fig. 3 is a cross-sectional view showing an example of the ion exchange membrane of the present invention. As shown in Fig. 3, an ion exchange membrane 10 has an electrolyte 12 consisting of a layer 12A, which is a layer (Sa), and a layer 12B, which is a layer (Sb), and an inorganic particle layer 14 disposed on the surface of the layer 12A, and a reinforcing material 20 is disposed in the electrolyte membrane 12. As shown in Fig. 3, the surface of the layer 12A on the inorganic particle layer 14 side has an uneven structure.

[0121] The ion exchange membrane of the present invention has the same configuration as the catalyst-layered ion exchange membrane of the present invention, except that it does not have the catalyst layer that the catalyst-layered ion exchange membrane of the present invention has, and the preferred embodiments are also the same. The details of each layer of the ion exchange membrane of the present invention are similar to those of the catalyst-layer-attached ion exchange membrane of the present invention, and therefore the description thereof will be omitted.

[0122] The method for producing the ion exchange membrane of the present invention is not particularly limited. For example, the ion exchange membrane can be obtained by carrying out steps other than step (iv) among steps (i) to (iv) shown as an example of the method for producing the ion exchange membrane with a catalyst layer of the present invention described above. The ion exchange membrane of the present invention is suitably used for producing the catalyst layer-attached ion exchange membrane of the present invention.

[0123] [Electrolytic hydrogenation equipment] The electrolytic hydrogenation apparatus of the present invention comprises an electrolytic cell equipped with an anode and a cathode, and the catalyst-layered ion exchange membrane of the present invention, wherein the catalyst-layered ion exchange membrane is disposed in the electrolytic cell so as to separate the anode and the cathode, the inorganic particle layer of the catalyst-layered ion exchange membrane is disposed on the anode side, and the catalyst layer of the catalyst-layered ion exchange membrane is disposed on the cathode side. The electrolytic hydrogenation apparatus of the present invention has the above-mentioned catalyst layer-equipped ion exchange membrane, and therefore can reduce the electrolysis voltage and increase the current efficiency during the electrolytic hydrogenation of aromatic compounds.

[0124] One embodiment of the electrolytic hydrogenation apparatus of the present invention will be described with reference to Fig. 4. Fig. 4 is a schematic diagram showing one example of the electrolytic hydrogenation apparatus of the present invention. As shown in FIG. 4, the electrolytic hydrogenation apparatus 100 comprises an electrolytic cell 110 equipped with a cathode 112 and an anode 114, and an ion exchange membrane 1 with a catalyst layer that is installed in the electrolytic cell 110 so as to separate the inside of the electrolytic cell 110 into a cathode chamber 116 on the cathode 112 side and an anode chamber 118 on the anode 114 side. As shown in FIG. 4, the catalyst-coated ion exchange membrane 1 is installed in an electrolytic cell 110 such that the inorganic particle layer 14 faces the anode 114 and the catalyst layer 16 faces the cathode 112.

[0125] The cathode 112 may be disposed in contact with the catalyst layer-coated ion exchange membrane 1, or may be disposed with a gap between the cathode 112 and the catalyst layer-coated ion exchange membrane 1.

[0126] The material constituting the cathode 112 and the cathode chamber 116 is preferably stainless steel, nickel, or the like. The anode 114 and the anode chamber 118 may be made of a material such as stainless steel or nickel. The surfaces of the electrode substrates, such as the cathode 112 and the anode 114, are preferably coated with, for example, ruthenium oxide, iridium oxide, or the like.

[0127] When aromatic compounds are electrolytically hydrogenated using the electrolytic hydrogenation device 100, an aqueous electrolytic solution is supplied to the anode chamber 118 in which the anode 114 is arranged, and the aromatic compounds are supplied to the cathode chamber 116 in which the cathode 112 is arranged. Specific examples of aromatic compounds include benzene, toluene, and naphthalene. The aqueous electrolyte solution is a solution in which an electrolyte is dissolved in water. Examples of the electrolyte include sulfuric acid and nitric acid. The concentration of the electrolyte is not particularly limited.

[0128] When the electrolytic hydrogenation apparatus 100 is operated, protons (H + ) moves through the catalyst-layered ion exchange membrane 1 to the cathode chamber 116. Then, near the surface of the catalyst layer 16, hydrogenation of the aromatic compound occurs due to proton addition, and a hydrogenated organic compound is obtained in the cathode chamber 116. Specific examples of hydrogenated organic compounds include cyclohexane, methylcyclohexane, and decahydronaphthalene. EXAMPLES

[0129] The present invention will be described in detail below with reference to examples. Examples 1 to 8 are working examples, and Examples 9 to 12 are comparative examples. However, the present invention is not limited to these examples.

[0130] [Thickness of each layer of the catalyst-coated ion-exchange membrane, and ion-exchange capacity of the fluoropolymer] The measurements were carried out according to the method described above.

[0131] [Evaluation test of electrolysis voltage and current efficiency] Effective current area is 1.5dm 2 The ion exchange membrane-anode assembly with a catalyst layer was placed in a test electrolytic cell (electrolysis surface size: 150 mm length x 100 mm width) so that the surface without the catalyst layer faced the anode. The anode used was an electrode made of SUS304 punched metal (minor diameter 5 mm, major diameter 10 mm) with electrodeposited Raney nickel containing ruthenium. The anode and the ion exchange membrane with the catalyst layer were placed so that they were in direct contact with each other and no gaps were generated. The flow rate of toluene supplied to the cathode chamber was adjusted to 5 mL / min, and the flow rate of 1 M aqueous sulfuric acid solution supplied to the anode chamber was adjusted to 10 mL / min. The temperature was 65°C, and the current density was 400 mA / cm. 2 Under the above conditions, electrolytic hydrogenation of toluene was carried out, and the electrolysis voltage (V) and current efficiency (%) were measured one day after the start of operation and evaluated according to the following criteria. (Electrolysis voltage) ◎:2.3V or less ○: More than 2.3V, less than 2.4V ×: More than 2.4V (current efficiency) ◎: 98% or more ○: 96% or more but less than 98% ×: Less than 96%

[0132] [Production of Fluorine-Containing Polymer (S1')] CF2 =CF 2 and a monomer (X) represented by the following formula (X) were copolymerized to obtain a fluorine-containing polymer (S1') (ion exchange capacity: 0.65 meq / g dry resin). CF 2 =CF-O-CF 2 CF(CF 3 )-O-CF 2 CF 2 -SO 2 F (X)

[0133] [Production of Fluorine-Containing Polymer (S2')] CF 2 =CF 2 and monomer (X) were copolymerized to obtain a fluorine-containing polymer (S2') (ion exchange capacity: 0.80 meq / g dry resin).

[0134] [Production of Fluorine-Containing Polymer (S3')] CF 2 =CF 2 and monomer (X) were copolymerized to obtain a fluorine-containing polymer (S3') (ion exchange capacity: 1.00 meq / g dry resin).

[0135] [Production of Fluorine-Containing Polymer (S4')] CF 2 =CF 2 and monomer (X) were copolymerized to obtain a fluorine-containing polymer (S4') (ion exchange capacity: 1.10 meq / g dry resin).

[0136] [Production of Fluorine-Containing Polymer (S5')] CF 2 =CF 2 and monomer (X) were copolymerized to obtain a fluorine-containing polymer (S5') (ion exchange capacity: 1.25 meq / g dry resin).

[0137] The ion exchange capacities described in the above [Production of fluoropolymer (S1')] to [Production of fluoropolymer (S5')] represent the ion exchange capacities of the fluoropolymers obtained by hydrolyzing the fluoropolymers (S1') to (S5') by the procedure described below.

[0138] [Production of Film A] The fluoropolymer (S1') was molded by melt extrusion to obtain a film A (thickness: 20 µm) made of the fluoropolymer (S1').

[0139] [Manufacturing of Film B] The fluoropolymer (S2') was molded by melt extrusion to obtain a film B (thickness: 20 µm) made of the fluoropolymer (S2').

[0140] [Production of Film C] The fluoropolymer (S3') was molded by melt extrusion to obtain a film C (thickness: 20 µm) made of the fluoropolymer (S3').

[0141] [Production of Film D] The fluoropolymer (S3') was molded by melt extrusion to obtain a film D (thickness: 40 µm) made of the fluoropolymer (S3').

[0142] [Production of Film E] The fluoropolymer (S3') was molded by melt extrusion to obtain a film E (thickness: 80 µm) made of the fluoropolymer (S3').

[0143] [Production of Film F] The fluoropolymer (S4') was molded by melt extrusion to obtain a film F (film thickness: 20 µm) made of the fluoropolymer (S4').

[0144] [Manufacturing of Film G] The fluoropolymer (S4') was molded by melt extrusion to obtain a film G (thickness: 80 µm) made of the fluoropolymer (S4').

[0145] [Manufacturing of Film H] The fluoropolymer (S5') was molded by melt extrusion to obtain a film H (thickness: 80 µm) made of the fluoropolymer (S5').

[0146] [Production of Film I] The fluoropolymer (S5') was molded by melt extrusion to obtain a film I (thickness: 100 µm) made of the fluoropolymer (S5').

[0147] [Manufacturing of reinforcing fabric] 50 denier PTFE yarns were used for the warp and weft, and plain weaving was performed so that the density of the PTFE yarns was 80 threads / inch to obtain woven fabric 1. The basis weight of woven fabric 1 was 38 g / m 2 The warp and weft were made of slit yarns.

[0148] [Preparation of inorganic particle paste] An inorganic particle paste (inorganic particle dispersion) was obtained by mixing 29.0 mass % of zirconium oxide (average particle size: 1 μm), 1.3 mass % of methylcellulose, 4.6 mass % of cyclohexanol, 1.5 mass % of cyclohexane, and 63.6 mass % of water.

[0149] [Example 1] Film A, reinforcing cloth, film I, and a release PET film (thickness: 100 μm) were layered in that order, and the release PET film was placed facing down and heated in a thermostatic chamber set to 220°C while vacuum-suctioning the air between films A and I to integrate the layers. The release PET film was then peeled off to obtain reinforced precursor film 1-1. Next, the inorganic particle paste was transferred to the surface of the film A of the electrolyte membrane by roll pressing to obtain a reinforced precursor membrane 1-2 in which an inorganic particle layer was disposed on the surface of the film A. The amount of zirconium oxide attached was 20 g / m 2 It was decided. The reinforced precursor membrane 1-2 was immersed in a solution of dimethyl sulfoxide / potassium hydroxide / water = 30 / 5.5 / 64.5 (mass ratio) at 95 ° C for 30 minutes to hydrolyze the groups in the reinforced precursor membrane 1-2 that can be converted to sulfonic acid functional groups to K-type sulfonic acid functional groups, and then washed with water. The obtained membrane was then immersed in 1 M sulfuric acid to convert the terminal groups from K-type to H-type, and then dried to obtain the ion exchange membrane 1.

[0150] TFE and the above monomer (X) were copolymerized, and the polymer (ion exchange capacity: 1.10 milliequivalents / g dry resin) was converted to an acid form through hydrolysis and acid treatment. The polymer was dispersed in a solvent of water / ethanol = 40 / 60 (mass %) at a solid content concentration of 25.8% to obtain a dispersion (hereinafter also referred to as "dispersion X"). Water (59.4 g) and ethanol (39.6 g) were added to a supported catalyst (Tanaka Kikinzoku Kogyo Co., Ltd.'s "TEC10E50E") (11 g) in which 46 mass% platinum was supported on carbon powder, and the mixture was mixed and pulverized using an ultrasonic homogenizer to obtain a catalyst dispersion. To the catalyst dispersion, a mixture (29.2 g) of Dispersion X (20.1 g), ethanol (11 g), and Zeorola-H (manufactured by Zeon Corporation) (6.3 g) was added. Water (3.66 g) and ethanol (7.63 g) were added to the resulting dispersion, and the mixture was mixed for 60 minutes using a paint conditioner to adjust the solid content to 10.0 mass %, to obtain a cathode catalyst ink (catalyst dispersion). The cathode catalyst ink was applied to an ETFE sheet using a die coater, dried at 80°C, and then heat-treated at 150°C for 15 minutes to obtain a platinum content of 0.4 mg / cm. 2 Thus, a cathode catalyst layer decal of 1000 nm was obtained. The surface of the ion exchange membrane 1 on which no inorganic particle layer was formed was placed opposite the surface of the cathode catalyst layer decal on which the catalyst layer was present, and the ion exchange membrane 1 and the cathode catalyst layer were bonded together by hot pressing under conditions of a pressing temperature of 150°C, a pressing time of 2 minutes, and a pressure of 3 MPa, and the temperature was lowered to 70°C, and then the pressure was released and the membrane was removed, and the ETFE sheet of the cathode catalyst layer decal was peeled off to obtain the ion exchange membrane with catalyst layer of Example 1 having a catalyst layer. Carbon felt was bonded as a cathode to the surface of the catalyst layer of the obtained ion exchange membrane, to obtain an ion exchange membrane-cathode assembly with a catalyst layer. The cathode area of ​​the catalyst-layered ion-exchange membrane-cathode assembly is 25 cm 2 It was.

[0151] [Example 2] Films F and H were heat-pressed together to obtain multilayer film FH. Film A, reinforcing cloth, multilayer film FH, and release PET film (thickness: 100 μm) were layered in that order, and the release PET film was placed facing down and heated in a thermostatic chamber set to 220°C while vacuum-suctioning the air between film A and multilayer film FH to integrate the layers. The release PET film was then peeled off to obtain reinforced precursor film 2-1. The multilayer film FH was arranged so that the film F side faced the reinforcing fabric side. An ion-exchange membrane-cathode assembly with a catalyst layer of Example 2 was obtained in the same manner as in Example 1, except that the reinforced precursor membrane 2-1 was used instead of the reinforced precursor membrane 1-1.

[0152] [Example 3] Film C and film H were heat-pressed together to obtain multilayer film CH. Except for using the multilayer film CH instead of the multilayer film FH, the ion exchange membrane-cathode assembly with a catalyst layer of Example 3 was obtained in the same manner as in Example 2. The multilayer film CH was arranged so that the film C side was on the reinforcing fabric side.

[0153] [Example 4] Films C and G were heated and pressed together to obtain multilayer film CG. Except for using the multilayer film CG instead of the multilayer film FH, a catalyst layer-attached ion exchange membrane-cathode assembly of Example 4 was obtained in the same manner as in Example 2. The multilayer film CG was arranged so that the film C side was the reinforcing fabric side.

[0154] [Example 5] Film B and film E were heat-pressed together to obtain multilayer film BE. Except for using the multilayer film BE instead of the multilayer film FH, a catalyst layer-attached ion exchange membrane-cathode assembly of Example 5 was obtained in the same manner as in Example 2. The multilayer film BE was arranged so that the film B side was on the reinforcing fabric side.

[0155] [Example 6] Film C and film H were heat-pressed together to obtain multilayer film CH. An ion exchange membrane-cathode assembly with a catalyst layer of Example 6 was obtained in the same manner as in Example 2, except that multilayer film CH was used instead of multilayer film FH and film B was used instead of film A. The multilayer film CH was arranged so that film C was on the reinforcing fabric side.

[0156] [Example 7] An ion exchange membrane-cathode assembly with a catalyst layer of Example 7 was obtained in the same manner as in Example 1, except that Film D was used instead of Film A and Film H was used instead of Film I.

[0157] [Example 8] An ion-exchange membrane-cathode assembly with a catalyst layer of Example 8 was obtained in the same manner as in Example 3, except that no reinforcing cloth was used.

[0158] [Example 9] An ion exchange membrane-cathode assembly with a catalyst layer of Example 9 was obtained in the same manner as in Example 3, except that no inorganic particle layer was provided on the surface of the film A.

[0159] [Example 10] An ion exchange membrane-cathode assembly with a catalyst layer of Example 10 was obtained in the same manner as in Example 1, except that a film J (product name "Nafion115", Chemours) was used instead of the ion exchange membrane 1.

[0160] [Example 11] An inorganic particle layer was formed on one surface of film J (product name "Nafion115", Chemours, a membrane composed of a fluorine-containing polymer having sulfonic acid groups) in the same manner as in Example 1, to obtain film J with an inorganic particle layer. An ion exchange membrane-cathode assembly with a catalyst layer of Example 11 was obtained in the same manner as in Example 1, except that Film J with an inorganic particle layer was used. The catalyst layer was formed on the surface of Film J opposite to the inorganic particle layer.

[0161] [Evaluation Results] The ion exchange membrane with the catalyst layer obtained as described above was used in various evaluation tests. The evaluation results are shown in Table 1. In Table 1, "IEC" means the ion exchange capacity of the fluoropolymer. In Table 1, "film thickness" means the film thickness of each layer in the ion exchange membrane with a catalyst layer, and was the same as the film thickness of each film used in producing the ion exchange membrane with a catalyst layer. In Table 1, "low IEC layer" refers to the layer made of a fluoropolymer with the lowest ion exchange capacity in the electrolyte membrane constituting the catalyst-layered ion exchange membrane, i.e., layer (Sa). Also, "high IEC layer" refers to the layer containing a fluoropolymer with a higher ion exchange capacity than the "low IEC layer", i.e., layer (Sb), in the electrolyte membrane constituting the catalyst-layered ion exchange membrane. However, when one type of film was used as the electrolyte membrane, the type of film used is listed in the "low IEC layer" column.

[0162] [Table 1]

[0163] As shown in Table 1, by forming the electrolyte membrane into a multi-layer structure, disposing a layer containing a fluorine-containing polymer with low ion exchange capacity (low IEC layer) on the anode side, and providing an inorganic particle layer on the surface of the low IEC layer, it was shown that the electrolysis voltage can be lowered and the current efficiency can be increased during the electrolytic hydrogenation of aromatic compounds (Examples 1 to 8).

[0164] Furthermore, using the ion exchange membrane with a catalyst layer of Example 1, carbon felt was bonded as a cathode to the surface of the inorganic particle layer to obtain an ion exchange membrane with a catalyst layer-cathode assembly of Example 12. When the surface of the ion exchange membrane with a catalyst layer of Example 12, in which the surface on which the inorganic particle layer was formed (i.e., the film A side) was placed on the cathode side and the surface on which the catalyst layer was formed (i.e., the film I side) was placed on the anode side, and an evaluation was carried out in the same manner as in Example 1, the voltage rose sharply and electrolytic hydrogenation could not be carried out. This is believed to be due to peeling between film A and film I. The entire contents of the specification, claims, drawings and abstract of Japanese Patent Application No. 2020-018828, filed on February 6, 2020, are hereby incorporated by reference as the disclosure of the present invention. [Explanation of symbols]

[0165] 1. Ion exchange membrane with catalyst layer 10 Ion exchange membrane 12 Electrolyte membrane 12A layer (Sa) 12B layer (Sb) 14 Inorganic particle layer 16 Catalyst layer 20 Reinforcement 22 Reinforcing thread 24 Sacrificial Thread 26 Filament 28 Elution hole 100 Electrolytic hydrogenation equipment 110 Electrolytic cell 112 Cathode 114 Anode 116 Cathode Chamber 118 Anode chamber B, B1, B2 convex part D1,D2 Shortest distance P1,P2 Position T1, T2 Position

Claims

1. an inorganic particle layer including inorganic particles and a binder; a layer (Sa) containing a first fluorine-containing polymer having a sulfonic acid functional group; a layer (Sb) containing a second fluorine-containing polymer having a sulfonic acid functional group; a catalyst layer, An ion exchange membrane with a catalyst layer, wherein the ion exchange capacity of the first fluoropolymer is lower than the ion exchange capacity of the second fluoropolymer.

2. The ion exchange membrane with a catalyst layer according to claim 1 , wherein the layer (Sa) has an uneven structure at an interface on the inorganic particle layer side.

3. The ion exchange membrane with a catalyst layer according to claim 1 or 2, further comprising a reinforcing material containing a reinforcing thread.

4. 4. The ion exchange membrane with a catalyst layer according to claim 1, wherein the ion exchange capacity of the first fluoropolymer is 0.5 to 1.1 milliequivalents / gram of dry resin.

5. 5. The ion exchange membrane with a catalyst layer according to claim 1, wherein the ion exchange capacity of the second fluoropolymer is 0.7 to 2.0 milliequivalents / gram of dry resin.

6. The catalyst layer-attached ion exchange membrane according to any one of claims 1 to 5, wherein the first fluorine-containing polymer having a sulfonic acid type functional group contains a unit based on a fluorine-containing olefin, and a unit having a sulfonic acid type functional group and a fluorine atom.

7. 7. The ion exchange membrane with a catalyst layer according to claim 6, wherein the fluorine-containing olefin is tetrafluoroethylene, chlorotrifluoroethylene, vinylidene fluoride, vinyl fluoride or hexafluoropropylene.

8. 8. The ion exchange membrane with a catalyst layer according to claim 6, wherein the unit having a sulfonic acid type functional group and a fluorine atom is a unit represented by formula (1): Formula (1) -[CF 2 -CF(-L-(SO 3 M) n )- In the formula, L is an (n+1) valent perfluorohydrocarbon group which may contain an etheric oxygen atom, M is a hydrogen atom, an alkali metal or a quaternary ammonium cation, and n is 1 or 2.

9. an inorganic particle layer including inorganic particles and a binder; a layer (Sa) containing a first fluorine-containing polymer having a sulfonic acid functional group; a layer (Sb) containing a second fluorine-containing polymer having a sulfonic acid functional group, An ion exchange membrane, wherein the ion exchange capacity of the first fluoropolymer is lower than the ion exchange capacity of the second fluoropolymer.

10. The ion exchange membrane according to claim 9 , wherein the layer (Sa) has an uneven structure at an interface on the inorganic particle layer side.

11. The ion exchange membrane according to claim 9 or 10, further comprising a reinforcing material comprising a reinforcing thread.

12. The ion exchange membrane according to any one of claims 9 to 11, wherein the first fluoropolymer has an ion exchange capacity of 0.5 to 1.1 milliequivalents per gram of dry resin.

13. The ion exchange membrane according to any one of claims 9 to 12, wherein the second fluoropolymer has an ion exchange capacity of 0.7 to 2.0 milliequivalents per gram of dry resin.

14. A method for producing an ion exchange membrane with a catalyst layer according to any one of claims 1 to 8, comprising the steps of: A method for producing an ion exchange membrane with a catalyst layer, comprising obtaining the ion exchange membrane according to claim 9 and providing a catalyst layer on the layer (Sb).

15. an electrolytic cell including an anode and a cathode; The catalyst layer-attached ion exchange membrane according to any one of claims 1 to 8, the catalyst layer-equipped ion exchange membrane is disposed in the electrolytic cell so as to separate the anode and the cathode; an electrolytic hydrogenation apparatus, wherein the inorganic particle layer of the catalyst-coated ion exchange membrane is disposed on the anode side, and the catalyst layer of the catalyst-coated ion exchange membrane is disposed on the cathode side.

16. 16. The electrolytic hydrogenation apparatus according to claim 15, wherein an aqueous electrolyte solution is supplied to an anode chamber in which the anode is disposed, and an aromatic compound is supplied to a cathode chamber in which the cathode is disposed.

Citation Information

Patent Citations

  • Distance measuring device

    JP1989000410A